CORRELATION AND COMPARISON OF SERUM CYSTATIN C WITH SERUM CREATININE IN KIDNEY FUNCTION - ANIMAL MODEL - MRS. SHOBHA M; DR. SHANTHI NAIDU K; MUJAHID M (International Journal of Pharma and Bio Sciences, 2016)
Contrast Induced Nephropathy (CIN) is a complication that is underestimated in clinical practice after cardiac catheterization. Recently, Cystain C as a novel biomarker for the detection of acute kidney injury has been highlighted. The current study proved that serum Cystatin C is a better marker of GFR (Glomerular Filtration Rate) when compared to that of Creatinine in contrast based Acute Kidney Injury (AKI). 30 animals were randomly divided into 10 different cages having 3 animals each and cages were randomly divided into 5 different groups. Animals were injected iohexol (Contrast) 350 mg Iodine/kg bodyweight as per the weight of animal intraperitoneally. Blood samples were collected before and after inducing contrast and centrifuged. Serum was stored at -200Cfor further analysis. Results shown were that the Cystatin C is an earlier marker for AKI when compared to Creatinine. Cystatin C levels were observed to be elevated at 3Hours where as elevation in Creatinine was at 12 Hours and hence statistically significant P<0.05 with unpaired test. Current study evaluated that the raise of serum Cystatin C is an earlier marker of glomerular filtation rate (GFR) which can be probably correlated with contrast based AKI.